CAFF Technical Report No. 13 - Distribution of Murres Outside the Breeding Season “Circumpolar Murre Banding Program” - Arctic Council, Conservation of Arctic Flora and Fauna Working Group (Conservation of Arctic Flora and Fauna Working Group (CAFF), 2004)
Arctic Council's CAFF Workign Group's Technical Report No. 13 - Distribution of Murres Outside the Breeding Season “Circumpolar Murre Banding Program”. This is a CIRCUMPOLAR SEABIRD GROUP (CBird)CAFF Expert Group publication.